Development of KASP markers, SNP fingerprinting and population structure analysis of Robinia pseudoacacia and its closely related species - Wang, Haoran; Wang, Ruixue; Zheng, Huizhong; Zhao, Chunlei; Zang, Dekui; Ma, Yan; Zang, Fengqi; Wu, Qichao (Frontiers in Plant Science, 2026)
Robinia pseudoacacia is a deciduous arbor with significant ecological and economic values. However, the current method for germplasm identification using fingerprinting primarily relies on traditional SSR markers, which suffer from limited polymorphism and cumbersome workflow. These drawbacks have hindered the development of genetic breeding in R. pseudoacacia. The present study aims to screen high-quality single nucleotide polymorphism (SNP) loci, develop reliable kompetitive allele-specific PCR (KASP) markers for genotyping R. pseudoacacia and its closely related species, further construct fingerprint profiles, and conduct genetic diversity analysis. The ultimate goal is to achieve accurate identification of R. pseudoacacia germplasm. In the present study, based on the single nucleotide polymorphism (SNP) loci identified through resequencing data alignment, 145 high-quality loci were screened out. Among these, 65 loci were selected for KASP marker development, and 31 core KASP markers were successfully developed ultimately. Genetic diversity and population structure of 105 R. pseudoacacia individuals and their related species in Daqingshan Forest Farm were analyzed using these KASP markers. The results showed that the polymorphism information content (PIC), minor allele frequency (MAF), gene diversity, and heterozygosity of the 31 core KASP markers were 0.335, 0.328, 0.428, and 0.357, respectively. The results of population structure analysis, principal component analysis (PCA), and phylogenetic tree analysis indicated that the 105 accessions could be clustered into three groups. Finally, a fingerprint profile was constructed for the 105 accessions of R. pseudoacacia and its closely related species based on the 31 core KASP markers, and all 105 accessions could be completely distinguished using only 12 of these markers. The KASP primers developed in this study provide a foundation for subsequent germplasm identification and genetic research of R. pseudoacacia.